2018
DOI: 10.1021/acs.jpca.7b11769
|View full text |Cite
|
Sign up to set email alerts
|

Ionization and Single and Double Electron Capture in Proton–Ar Collisions

Abstract: Total cross sections for formation of H and H, and electron production, in H + Ar collisions have been calculated at energies between 100 eV and 200 keV by employing two methods: for E < 10 keV, a semiclassical treatment with an expansion in a basis of electronic wave functions of the ArH quasimolecule and, for E > 10 keV, the switching-classical-trajectory-Monte Carlo method (s-CTMC). The semiclassical calculation involves transitions to molecular autoionizing states, calculated by applying a block-diagonaliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 80 publications
0
3
0
Order By: Relevance
“…Although experimental work rarely achieves this, the long effort on theoretical treatment of charge exchange has greatly progressed [47][48][49][50], particularly with the computational capability needed for treating the quasi-molecular intermediate state formed by the incident ion and target as a result of the incident ion being of much lower velocity than the orbital electrons of the target (Born-Oppenheimer approximation). For energies less than 1 keV the Molecular Orbital Close Coupling Method (MOCC) has worked well, though still computationally intensive [51][52][53]. Time dependent density functional theory is also promising [54].…”
Section: Resultsmentioning
confidence: 99%
“…Although experimental work rarely achieves this, the long effort on theoretical treatment of charge exchange has greatly progressed [47][48][49][50], particularly with the computational capability needed for treating the quasi-molecular intermediate state formed by the incident ion and target as a result of the incident ion being of much lower velocity than the orbital electrons of the target (Born-Oppenheimer approximation). For energies less than 1 keV the Molecular Orbital Close Coupling Method (MOCC) has worked well, though still computationally intensive [51][52][53]. Time dependent density functional theory is also promising [54].…”
Section: Resultsmentioning
confidence: 99%
“…Nevertheless, the comparison of the cross sections with the available experiments points to a limitation of the model for collision energies below 50 keV/u for all the oneelectron treatments, which is related to the independent electron approximation. Although an all-electron calculation of electron capture is feasible at low energies 57 , the connection with the results above 50 keV/u is difficult because the competition of electron capture and ionization processes at these energies (an illustration of this point for ion-atom collisions can be found in the work of Jorge et al 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…When the probability of re-moving the first electron is high, one can think that successive electron removals will take place with lower probabilities than those calculated in the single-electron calculation. In this respect, previous works on proton collisions with water molecules pointed out that the IEM overestimates the probability of removing two electrons from different shells, and suggested that an alternative interpretation, called the Independent Event Model (IEV), could be more appropriate (see Jorge et al 46 and references therein). Since both interpretations correspond to limit situations, it is difficult to predict a priori which one is more appropriate for a given process.…”
Section: Introductionmentioning
confidence: 99%